Teachers’ Voices on the Transition from Curriculum 2013 to Kurikulum Merdeka in Indonesian Elementary Schools - Novita Purnamasari Rahayu; Andi Rachmawati Syarif; Syarif Amin; Maulina; Sam Hermansyah (Universitas Islam Negeri Palopo, 2026)
Curriculum reform is a continuous process aimed at improving educational quality and responding to evolving societal needs. In Indonesia, the transition from Curriculum 2013 (K13) to Kurikulum Merdeka represents a major shift toward flexible, competency-based learning. However, the success of such reforms largely depends on teachers who serve as the primary implementers of curriculum policies. This study aims to explore elementary school teachers’ perceptions, challenges, and recommendations regarding the transition from K13 to Kurikulum Merdeka in Kendari, Indonesia. The research employed a descriptive survey design involving 31 public elementary school teachers who had experience teaching under both curricula. Data were collected through a structured questionnaire consisting of 25 items and analyzed using descriptive statistics and thematic analysis. The findings indicate that most teachers perceive Kurikulum Merdeka positively, particularly appreciating its flexibility in lesson planning and its emphasis on essential learning content. Nevertheless, teachers reported several challenges during implementation, including limited time, insufficient training, and inadequate school resources. Despite these challenges, the majority of respondents expressed strong support for the new curriculum and believed it has the potential to improve the quality of learning. Teachers also recommended increased professional development opportunities, collaborative teacher forums, and clearer implementation guidelines from education authorities. These findings highlight the importance of incorporating teachers’ voices into curriculum reform processes to ensure sustainable and effective implementation of Kurikulum Merdeka.